A comparative study of body potential transient profile of geosynchronous orbit spacecraft in single and double Maxwellian plasma models. (19th October 2021) - Pandya, Ashish; Kothari, Nikhil; Alad, Rizwan
Abstract: Estimation of the transient profile of body potential of spacecraft in recommended cases of plasma models is crucial because of its importance to estimate electrostatic discharge (ESD) events. The spacecraft structure consisting of a cuboid with two coplanar rectangular plates is modeled as a lumped equivalent capacitance circuit. Method of moments is used to compute absolute and coupled capacitances, which directly affect the transient profile of body potential. Additionally, closer to the actual plasma model representing substorm injection events is vital for reliable estimation of absolute charging. Accordingly, in this work, we attempt a comprehensive analysis of the charging of a spacecraft in Maxwellian plasma models with the inclusion of induced electron yields for the probable particle incidences. Subsequently, the critical range of particle energy susceptible to failures related to ESD is investigated for a spacecraft structure of Aluminum. The comparison of transient variations of body potential in single and double Maxwellian plasma environments identifies the critical aspects of normal and worst cases concerning the prediction of ESD events, which can be useful in the early stage of a spacecraft design.